Penerapan model pembelajaran kooperatif tipe TAI pada materi bentuk aljabar di kelas VII SMP Negeri 3 Banda Aceh (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The main purpose of this study was to determine student learning outcomes using the TAI type cooperative learning model on algebraic form material in class VII SMP Negeri 3 Banda Aceh. To support the main purpose of this study, researchers used data supporting student activities to see student activities in learning. The population in this study were all VII grade students totaling 254 students and the sample was Class VII4, namely 28 students of SMP Negeri 3 Banda Aceh. This type of research in this study is a pre-experimental study with the type of one-shot case study with a quantitative approach. The main data were collected using test results data and for supporting data observation sheets were used. The data obtained were analyzed using test-t. Based on data processing obtained  = 79.21,   and so at a significant level. Based on the testing criteria of student learning outcomes using the TAI type cooperative learning model can exceed the value of the minimum completeness criteria (KKM) and obtained student activity on algebraic form material in class VII SMPN 3 Banda Aceh is active.
Keywords: TAI Type Cooperative Learning Model; Algebra Form